Individuals with Psychopathic Traits view Distracting Neutral Information as Negatively Valenced. Issue 1 (2nd January 2018) - Tillem, Scott; Baskin-Sommers, Arielle
ABSTRACT: Research has shown that psychopathic individuals ignore information that is outside their goal-directed focus of attention. When affective information is goal-irrelevant, ignoring it results in a blunted affective response for psychopathic individuals. In cognitive science, though, an interesting phenomenon named inhibitory devaluation occurs in the context of neutral information. When neutral information is not relevant to a goal, ignoring it actually results in individuals' evaluating the neutral information as negatively valenced. In a sample of adult male offenders ( N = 82), we used a pattern localizer task to examine the relationship between inhibitory devaluation and psychopathy (using scores on the Psychopathy Checklist-Revised). Results indicated that individuals high on the interpersonal-affective traits of psychopathy displayed significantly greater inhibitory devaluation, meaning that they ascribed more affective valence to goal-irrelevant neutral information. This finding provides further support for the importance of attention abnormalities in the neurobiology of psychopathy-related affective and interpersonal deficits.